Penanaman Pohon Pelindung sebagai Upaya Penghijauan Lingkungan - Nita, Yureya; Nastiti, Retno; Ananta, Azra; Nurhaliza, Nurhaliza (LPPM Universitas Bumigora, 2023)
Planting shade trees is useful for preventing landslides on the ground and can be used as a flood prevention. This greening is not only done to prevent various kinds of natural disasters, but also as a protectorof the surrounding environment to avoid bad air pollution. This is closely related to the government's policy that the Indonesian people plant 25 trees while they are alive. Considering that Indonesia is the largest contributor of oxygen in the world, quality oxygen is needed for the survival of living things on this earth. Indonesia also has the largest forests so that they become the lungs of the world. Tree planting is carried out in Kelurahan Air Dingin, Pekanbaru City, Riau. The planting of this shade tree consists of matoa trees, mahogany trees and trembesi trees. The greening activity was carried out jointly with community leaders and residents of the Kelurahan Air Dingin on Friday, December 23, 2022. The results of this tree planting activity received appreciation and support from the Lurah, RW, RT and residents of Kelurahan Air Dingin. This tree planting activity succeeded in planting 15 trees consisting of 5 mahogany trees, 5 matoa trees, and 5 trembesi trees.